ECONOMIC LIBERALIZATION: OPENNESS AND INTEGRATION — BUT WHAT KIND? - Edith T. Penrose (Prometheus, 1993)
In advanced industrial economies… managerial hierarchies have gained an increasing advantage over market mechanisms or multilateral negotiations in coordinating the flow of goods, monitoring economic activities, and allocating resources… By the time the United States entered World War I management decisions had replaced coordination by market forces in many of the most critical sectors of the economy. The result might be termed managerial capitalism. (Chandler and Daems, 1980: 5, 6) … the decision-taking nexus of the MNE in the late 1980s has come to resemble the central nervousd system of a much larger group of interdependent but less formally governed activities, whose function is primarily to advance the global competitive strategy and position of the core organization … There are several implications of the new style MNEs… First they cause us to reappraise our thinking about the nature, function and boundaries of firms and markets… Second, they cast doubt on the usefulness of some of our existing classifications of our economic activities and of our traditional concepts of competition. Third, they have profoundly affected the pattern and ownership of international economic activity and the political economy of the countries which are party to it. (Dunning, 1988a: 327, 328) The first element of a successful industrial policy is the creative use and shaping of the market. Industrial policy fails when it overrides or ignores the market and is based upon the presumption that plans and markets are alternative means of economic coordination … The market, it has been said, is a good servant, but a bad master… effective policy towards industry depends on breaking with the plan or market dichotomy that informs conventional economic theory and is taken for granted by policy makers guided by that theory. (Best, 1990: 20)